Transcriptomic and biochemical evidence for the role of lysine biosynthesis against linoleic acid hydroperoxide-induced stress in Saccharomyces cerevisiae. (December 2014) - O'Doherty, P. J.; Lyons, V.; Tun, N. M.; Rogers, P. J.; Bailey, T. D.; Wu, M. J.
Abstract Amino acid biosynthesis forms part of an integrated stress response against oxidants in Saccharomyces cerevisiae and higher eukaryotes. Here we show an essential protective role of the l-lysine biosynthesis pathway in response to the oxidative stress condition induced by the lipid oxidant-linoleic acid hydroperoxide (LoaOOH), by means of transcriptomic profiling and phenotypic analysis, and using the deletion mutant dal80∆ and lysine auxotroph lys1∆. A comprehensive up-regulation of lysine biosynthetic genes (LYS1, LYS2, LYS4, LYS9, LYS12, LYS20 and LYS21) was revealed in dal80Δ following the oxidant challenge. The lysine auxotroph (lys1∆) exhibited a significant decrease in growth compared with that of BY4743 upon exposure to LoaOOH, albeit with the sufficient provision of lysine in the medium. Furthermore, the growth of wild type BY4743 exposed to LoaOOH was also greatly reduced in lysine-deficient conditions, despite a full complement of lysine biosynthetic genes. Amino acid analysis of LoaOOH-treated yeast showed that the level of cellular lysine remained unchanged throughout oxidant challenge, suggesting that the induced lysine biosynthesis leads to a steady-state metabolism as compared to the untreated yeast cells. Together, these findings demonstrate that lysine availability and its biosynthesis pathway play an important role in protecting the cell from lipid peroxide-induced oxidative stress, which is directly related to understanding environmental stress and industrial yeast management in brewing, wine making and baking.